Optimizing the production of wheat beer by recycling the yeast biomass: perspective for cost reduction with quality maintenance - PINTO-NETO, Walter de Paula; SILVA, Alice Kelly Leonardo Fernandes da; ARAÚJO, Katarynna Santos de; PINHEIRO, Irapuan Oliveira; SOUZA, Rafael Barros de; MORAIS JUNIOR, Marcos Antonio de (Food Science and Technology, 2023)
A considerable investment is being experienced worldwide in the production of artisanal beers of different styles, such as wheat-based Weizen beer. The challenge is to reduce production costs while maintaining the commercially accepted quality. Thus, the improvement of the production process involves the possibility of shortening the fermentation time by reusing the yeast biomass without affecting the yeast vitality and the quality of the end product. In this study, the fermentation parameters of a Weizen beer were measured directly from a scaled-up process in a microbrewing in order to identify the optimum point at which the process might be ended without compromising the final characteristics. The results were confirmed by laboratory studies that compared three different yeast strains in a wheat-based industrial substrate. The results led to the conclusion that the fermentation time was reduced by more than 50% from 7 to 3 days, with less variation in the concentration of the investigated metabolites. By reducing the time of fermentation, the yeast biomass was maintained active to be used up to six consecutive cycles of fermentation. All these improvements might help in reducing the cost of beer processing, which is of paramount interest to microbreweries worldwide.